Our Rightful Place : A History of Women at the University of Kentucky, 1880-1945 - Birdwhistell, Terry L.; Scaggs, Deirdre A. (Book collections on Project MUSE., 2020)
"In 1880, forty-three women walked into the president's office at the University of Kentucky (UK) and signed the student register, becoming the first female students at a public college in the commonwealth. But gaining admittance was only the beginning. For the next sixty-five years-encompassing two world wars, an economic depression, and the ratification of the Nineteenth Amendment-generations of women at UK claimed and reclaimed their right to an equitable university experience. Their work remains unfinished. Drawing on yearbooks, photographs, and other private collections, Our Rightful Place: A History of Women at the University of Kentucky, 1880-1945 examines the struggle for gender equity in higher education through the lens of one major institution. In the face of shifting resistance, pioneering women constructed opportunities for themselves. Terry L. Birdwhistell and Deirdre A. Scaggs highlight three women-Sarah Blanding, Frances Jewell McVey, and Sarah Bennett Holmes-who fought to secure basic facilities that were denied to UK women for decades, including housing and study spaces. By examining the trials and triumphs of UK's first female undergraduates, faculty, and administrators, this book uncovers the lasting impact women had on higher learning in the early days of coeducation"--